β-caryophyllene improves cerebral ischemia reperfusion injury in rats via Notch1/NF-κB signal axis - LIU Jingdong; CHEN Sha; WANG Yuchun; LIU Shengwei; RAO Jiangyan; WANG Qian; DENG Ling; WANG Xuan; DONG Zhi (Di-san junyi daxue xuebao, 2021)
Objective To explore the protective effect of β-caryophyllene (BCP) on cerebral ischemia-reperfusion (I/R) rats and related mechanism. Methods SD rats were randomized into sham operation group, I/R group, and low-, medium- and high-dose BCP groups (102, 204 and 408 mg·kg-1), Jagged1 (Notch1 agonist, 50 mg·kg-1 in 3 h before I/R injury)+BCP group, and Jagged1 group. The treatments were given to the corresponding rats through intragastric infusion. In 7 d later, SD rat CIR model was established with suture-occlusion, with ischemia for 1.5 h followed by reperfusion for 48 h. The infarct volume and neurobehavioral score were measured; Western blotting was used to detect the cerebral protein levels of Notch1, NF-κB p65, NF-κB p-p65 and Hes1; HE staining was applied to observe the number of dead cells, and ELISA was employed to detect the changes of TNF-α and IL1-β contents in the ischemic hippocampus. Results BCP treatment could significantly improve the neurological deficit, reduce the infarct volume, down-regulate the protein levels of Notch1, NF-κB and Hes1 in the hippocampus (P < 0.05), reduce the releases of TNF-α and IL-1β (P < 0.05), and attenuate the death of hippocampal neuronal cells in the rats after cerebral I/R injury. Comparing the simple Jagged1 intervention group, Notch1 agonist, Jagged1, could antagonize the therapeutic effects of BCP. Conclusion BCP can attenuate cerebral I/R injury in rats, and exerts its protective effect probably through inhibiting Notch1/NF-κB signal axis to reduce the release of inflammatory factors.